Hedging derivative securities with volatility futures - YAP, Kian Leong Nelson (Institutional Knowledge at Singapore Management University, 2016)
We show a method to replicate S&P 500 exchange traded fund (ETF) European synthetic put by optimally rebalancing a portfolio of the underlying ETF shares, the VIX futures contracts, and treasury bonds over discrete periods. The motivation for this study is two-fold. Firstly, market-makers in S&P 500 index options may need to hedge a large short position synthetically when the puts are in short supply. Secondly, for an institutional investor holding a large diversified portfolio of US stocks, constructing a long position in synthetic puts is tantamount to providing portfolio insurance. The put replication is useful as the alternative of buying US puts can be prohibitively expensive in a distressed market. The numerical method of Gauss-Hermite quadrature is employed in the optimal solution. Both simulations and empirical validation using historical S&P 500 index ETF and VIX futures price data show effectiveness in the put pricing versus more traditional methods.